Community participation and empowerment through Shora in Seyyedabad, Iran - Zomorrodian, Amir Hossein (2015)
The core idea of this thesis is to illustrate the role of Shora (local name for Community Based Organization in Iran) in order to develop and to enhance participation and empowerment in Seyyedabad community. In this respect, the study reviews participation in Shora activities, sense of community, perception about costs, benefits and leadership of Shora and empowerment of community members. The idea of the interrelation between these variables has been extracted from Zimmerman’s “theory of empowerment” and two extended theories, including McMillan and Chavis’ “sense of community” and “social exchange theory”. This research employs the use of the mixed method design (the explanatory design). The qualitative results of the study indicated three main functions for Shora including developmental programs, providing courses and routine issues. The qualitative results also illustrated five different types of participation processes in Seyyedabad, namely elite participation, representative participation, workforce donation, mass participation and attending classes. The quantitative results revealed all of the variables and sub-variables extracted from the conceptual framework,including perceived leadership, perceived benefits, perceived costs, sense of membership,influence, fulfillment of needs and emotional connection evinced a significant relationship with community members’ participation in Shora activities. Moreover,participation in Shora activities and sense of community had a significant relationship with the empowerment of community members. Furthermore, according to the results of the regression model variables namely sex,marital status, age, perception of Shora and community members’ sense of community predict 44 percent of participation in Shora activities. In addition,variables namely ethnicity, education, sense of community and participation in Shora predict 57 percent of the empowerment of community members. Finally, the combination of the results of the two phases of the research illustrates the fact that the Shora organization acts almost properly in order to enhance participation and empowerment of community members; however, there is a controversy lying here. Even though community members have a high perception of Shora and a high sense of community and these two variables encourage participation, community members only have the opportunity to involve in lower types of participation. These types of participation have limited effect on empowering them and this fact is the main reason for the inadequate empowerment within community members.